Psoriasis and Molecular Target Therapies: Evidence of Efficacy in Preventing Cardiovascular Comorbidities - Luca Potestio; Nello Tommasino; Giuseppe Lauletta; Fabrizio Martora; Matteo Megna (Adis, Springer Healthcare, 2024)
Abstract Psoriasis is now considered a systemic disease, and several comorbidities have been described such as cardiovascular diseases, neurologic and psychiatric disorders, chronic inflammatory bowel disease, psoriatic arthritis, etc. Regarding cardiovascular comorbidities, major adverse cardiovascular events have been reported in psoriasis patients by multiple epidemiologic studies. Moreover, smoking, obesity, metabolic syndrome, hypertension, dyslipidemia, diabetes and reduced physical activity are associated with psoriasis, increasing cardiovascular risk. Consequently, several aspects should be considered when making the treatment decision. The aim of this review manuscript was to investigate the effectiveness and safety of biologic drugs acting on molecular mechanisms involved in the pathogenesis of psoriasis in preventing cardiovascular complications.